Cannabinoids and neuroinflammation: Therapeutic implications - Brian E. Leonard; Feyza Aricioglu (Journal of Affective Disorders Reports, 2023)
This review summarizes the pharmacological properties of tetrahydrocannabinol (THC) and cannabidiol (CBD), cannabinoid components of several species of herbal cannabis. The pharmacological effects of the phytocannabinoids have been extensively investigated and the importance of the cannabinoid receptors (CB1 and CB2) on immune cells has provided important information on the intracellular targets for these molecules. In addition to the phytocannabinoids, endogenous cannabinoids also exist in the form of anadramide and 2-srodolylglycerol (2-AG). These, together with their synthesizing and metabolizing enzymes, form the cannabinoid system. Since the discovery of the endocannabinoid system and the role that neuroinflammation plays in neurological and psychiatric illness, the potential therapeutic importance of this system has been of growing interest. In addition, the need to develop drugs which specifically target the CB1 and CB2 receptors has been stimulated by the pharmacological complexity of both THC and CBD. This review briefly summarizes the therapeutic potential of the naturally occurring and the synthetic cannabinoids which will need to be developed, if such drugs are to fulfill the therapeutic promise which the cannabinoids offer.